miR172 Regulates WUS during Somatic Embryogenesis in Arabidopsis via AP2 - Katarzyna Nowak; Joanna Morończyk; Małgorzata Grzyb; Aleksandra Szczygieł-Sommer; Małgorzata D. Gaj (Cells, 2022)
In plants, the embryogenic transition of somatic cells requires the reprogramming of the cell transcriptome, which is under the control of genetic and epigenetic factors. Correspondingly, the extensive modulation of genes encoding transcription factors and miRNAs has been indicated as controlling the induction of somatic embryogenesis in Arabidopsis and other plants. Among the MIRNAs that have a differential expression during somatic embryogenesis, members of the MIRNA172 gene family have been identified, which implies a role of miR172 in controlling the embryogenic transition in Arabidopsis. In the present study, we found a disturbed expression of both MIRNA172 and candidate miR172-target genes, including AP2, TOE1, TOE2, TOE3, SMZ and SNZ, that negatively affected the embryogenic response of transgenic explants. Next, we examined the role of AP2 in the miR172-mediated mechanism that controls the embryogenic response. We found some evidence that by controlling AP2, miR172 might repress the WUS that has an important function in embryogenic induction. We showed that the mechanism of the miR172-AP2-controlled repression of WUS involves histone acetylation. We observed the upregulation of the WUS transcripts in an embryogenic culture that was overexpressing AP2 and treated with trichostatin A (TSA), which is an inhibitor of HDAC histone deacetylases. The increased expression of the WUS gene in the embryogenic culture of the hdac mutants further confirmed the role of histone acetylation in WUS control during somatic embryogenesis. A chromatin-immunoprecipitation analysis provided evidence about the contribution of HDA6/19-mediated histone deacetylation to AP2-controlled WUS repression during embryogenic induction. The upstream regulatory elements of the miR172-AP2-WUS pathway might involve the miR156-controlled SPL9/SPL10, which control the level of mature miR172 in an embryogenic culture.